The Effect of Oral Sildenafil on the Decrease in the Degree of Pulmonary Artery Systolic Pressure in PPHN Infants at Siti Khodijah Muhammadiyah Hospital Sepanjang - Afif, Muhammad; Airlangga, Muhammad Perdana; Yuliyanasari, Nurma; Djalilah, Gina Noor (MAGNA MEDIKA: Berkala Ilmiah Kedokteran dan Kesehatan, 2021)
Background: Persistent Pulmonary Hypertension of the Newborn (PPHN) is a condition of the failure to decrease pulmonary artery pressure, so that blood pressure in the lungs remains high, as in a fetus. PPHN cases are 2-6 of 1000 live births and responsible for 10% of confirmed deaths in the neonatal intensive care unit (NICU). Sildenafil is vasodilator that can be used to reduce pulmonary artery systolic pressure (PASP), morbidity, and mortality in PPHN infants.Objective: To analyze the effect of sildenafil on decrease the severity of pulmonary artery systolic pressure in PPHN infants.Method: This is an analytic observational study with cross-sectional design. The samples were collected using consecutive sampling on 30 PPHN infant patients in 2018. The data were collected from medical records of PPHN infant patients, then assessing the severity value of PASP which obtained from echocardiography result. The severity of PASP is classified into normal (PASPâ‰¤35 mmHg), mild (PASP36-45 mmHg), moderate (PASP 45-60 mmHg), and severe (PASP>60 mmHg)Results: This study showed that 27 PPHN infant patients have decreased PASP level to normal, previously from mild 7 infants (23.3%), moderate 16 infants (53.3%), and severe 4 infants (13%), after being given oral sildenafil. There were 1 (3.3%) infant patient remained severes, 1 (3.3%) patient was decreased from severe to moderate, and 1 patient (3.3%) was decreased from severe to mild. The p value <0.05 was obtained, so oral sildenafil significantly decreased the PASP severity in PPHN infants patients.Conclusion: There is a beneficial effect of oral sildenafil on decreasing the severity of pulmonary artery systolic pressure in PPHN infants at the NICU of Siti Khodijah Muhammadiyah Hospital Sepanjang.